2004
DOI: 10.1111/j.1745-6584.2004.tb02722.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rhodamine Water Tracer in the Marshland Upwelling System

Abstract: Rhodamine water tracer (RWT) was used to characterize the migration of waste water within the saline subsurface of a marshland upwelling system (MUS), which is an alternative on-site waste water treatment system for coastal areas. Field tracer studies were performed to investigate the fresh waste water plume movement within the saline ground water. Pore velocities were calculated using first detection times and ranged from 0.68 to 10.7 x 10(-4) cm/sec for the loamy sandy soil matrix present at the site. Use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(53 citation statements)
references
References 18 publications
0
52
0
1
Order By: Relevance
“…These results reveal the absence of RhB degradation in such mixtures. There was a slight loss, 8%, in non-irradiated suspensions due to the adsorption of RhB particles on the gelatin/CuS/PVA nanocomposite [10]. Also, it can be noted that the experiment in the absence of photocatalysts showed almost no RhB photodegradation, implying that the self photolysis of RhB is negligible when irradiated with visible light.…”
Section: Photocatalytic Activitymentioning
confidence: 84%
“…These results reveal the absence of RhB degradation in such mixtures. There was a slight loss, 8%, in non-irradiated suspensions due to the adsorption of RhB particles on the gelatin/CuS/PVA nanocomposite [10]. Also, it can be noted that the experiment in the absence of photocatalysts showed almost no RhB photodegradation, implying that the self photolysis of RhB is negligible when irradiated with visible light.…”
Section: Photocatalytic Activitymentioning
confidence: 84%
“…In order to determine the rate-limiting step of the BV 14 dye adsorption process onto the chemically modified nanofibers, the kinetic data was analyzed using the intraparticle diffusion model through the following equation [18] q t " k id t 1/2`I (8) where k id represents the intra-particle diffusion rate constant that relates to the boundary layer thickness. The plotting of the intraparticle diffusion model for the adsorption of BV 14 at different initial dye concentrations was illustrated in Figure 10.…”
Section: Kinetic Modeling Of Dye Sorption Process Onto Fabricated Funmentioning
confidence: 99%
“…The potential for turbidity to impact upon our field study was assessed by measuring a range of RWT solutions prepared using water from our field site, and no significant deviation from expected fluorescence was observed hence any possible effects of turbulence on RWT fluorescence measurements were ignored for the remainder of the study. A number of studies have also demonstrated that the use of RWT in quantitative studies may be compromised by photochemical decay of RWT over time (Smart and Laidlaw, 1977;Tai and Rathbun, 1988;Suijlen and Buyse, 1994;Upstill-Godard et al, 2001;Dierburg and C. H. Mines et al: Use of rhodamine WT as proxy for point source pollutants DeBusk, 2005) and loss of RWT due to adsorption (Smart and Laidlaw, 1977;Wilson et al, 1986;Sabatini and Austin, 1991;Shiau et al, 1993;Di Fazio and Vurro, 1994;Soerens et al, 1994;Kasnavia et al, 1999;Close et al, 2002;Keefe et al, 2004;Kung et al, 2000;Vasudevan et al, 2001;Lin et al, 2003;Pang et al, 2003;Richardson et al, 2004;Dierburg and DeBusk, 2005) but as the work described here focused on the use of RWT within a closed pipe surface water drainage network these potential losses were deemed insignificant and not re-examined. Given this range of potential compromising factors, the inconsistent nature of field results concerning RWT fate and transport (Tai and Rathbun, 1988;Jones and Jung, 1990;Suijlen and Buyse, 1994;Ptak and Schmid, 1996;Kung et al, 2000;Upstill-Godard et al, 2001;Close et al, 2002;Lin et al, 2003) is unsurprising.…”
Section: Introductionmentioning
confidence: 99%
“…The management of such contamination is complicated by difficulties in identifying point sources. Water tracers such as the xanthene dye Rhodamine WT (RWT) can be utilised in the investigation of contaminant transport in hydraulic systems to examine the transport of solutes (Broshears et al, 1996;Hibbs et al, 1998;Fox et al, 2002;Gaikowski et al, 2004;Richardson et al, 2004; Correspondence to: A. Ghadouani (anas.ghadouani@uwa.edu.au) Mukherjee et al, 2005), and thus trace contaminants back to their source (Pitt et al, 1993;Lalor and Pitt, 1999;Close et al, 2002;Pitt, 2002). Whilst information regarding time of travel and flow velocity may be determined through qualitative applications of tracers, quantitative tracing is required for more precise hydrological information such as potential contaminant transport characteristics.…”
Section: Introductionmentioning
confidence: 99%